Analysis of Student Errors in Learning Circle Based on the Watson Error Category - Ni Nyoman Riantini W.; I Nengah Suparta; I Gusti Putu Sudiarta (International Journal on Emerging Mathematics Education, 2020)
Error analysis is a process of reviewing students' answers to identify patterns of understanding. Errors in mathematics are considered as deviations from the actual solution of a problem. The aim of the study is to analyze student errors based on the Watson error category learning circle. In this study students were given 5 essay mathematical problems, and then analyzed their errors based on 8 Watson error categories and continued by interviewing 1 student for each category of error. This study was conducted at SMP PGRI 3 Denpasar in a class on IX grade with 40 students. The results show that the percentage of student errors categories obtained from this study as follows: comprehension errors 54%, transformation errors 18%, process skills errors 15%, encoding errors 7%. Students are interviewed to find out carelessness and motivation that affect students' mistakes. While for question form category we found no errors.Â